Pengaruh Leverage, Likuiditas, Profitabilitas, Ukuran Perusahaan, Dan Tingkat Pertumbuhan Perusahaan Terhadap Kebijakan Dividen (Studi Empiris Pada Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Vika Septirini; Ronny Malavia Mardani; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study to analyze the effect of leverage, liquidity, profitability, company size, and company growth rate on dividend policy in banks listed on the Indonesia Stock Exchange in 2017-2019. In this study, there are 5 (five) independent variables, namely leverage is proxied by debt to equity ratio (DER), liquidity is proxied by current ratio (CR), profitability is proxied by return on assets (ROA), company size, and company growth rate. The dependent variable in this study is dividend policy proxied by the dividend payout ratio (DPR). The population in this study were all banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period with a total of 44 banking companies. Sampling technique using purposive sampling method obtained a sample of data as many as 11 banking companies. The research data collection method uses the method of data documentation. The data analysis technique in this study used panel data regression with software eviews 9. The results showed that partially DER had a negative and insignificant effect on DPR. CR and Size each have a positive and non-significant effect. ROA and growth have a negative and significant effect on the DPR. Keywords: leverage, debt to equity ratio (DER), liquidity, current ratio (CR), profitability, return on assets (ROA), firm size, firm growth rate, dividend policy, dividend payout ratio (DPR).